Sleep and psychological characteristics in habitual self-awakeners and forced awakeners. (3rd April 2022) - Malloggi, S.; Conte, F.; Albinni, B.; Gronchi, G.; Ficca, G.; Giganti, F.
ABSTRACT: Previous studies described the modifications of physiological and behavioural variables associated with self-awakening, while only few studies assessed subjective sleep quality and psychological characteristics in habitual self-awakeners. Here we investigated self-reported sleep habits and features, as well as psychological variables of habitual self-awakeners and forced-awakeners, with special regard to subjective sleep quality, personality characteristics, anxiety and depression symptoms. In our sample, the prevalence of habitual self-awakeners was 15.1%. Compared to forced-awakeners, habitual self-awakeners showed more regular sleep/wake schedules and were more frequently morning types. Moreover, habitual self-awakeners referred to be more satisfied about their sleep, to wake up more easily in the morning, to need less time to get out of bed and to feel more refreshed upon awakening than forced-awakeners. We also observed an association between the habit of self-awakening and the "ability" to set the awakening to an unusual time. Concerning psychological features, habitual self-awakeners showed higher scores in Conscientiousness and Openness and lower scores in Extraversion compared to forced-awakeners, whereas no differences between groups emerged for anxiety and depression levels. In conclusion, our findings point to an association between the habit of self-awakening and good subjective sleep quality. In this perspective, future research should objectively test in detail the effects of the self-awakening habit on sleep structure and organization, taking into account also microstructural sleep features.